Longitudinal cerebellar growth following very preterm birth. Issue 6 (23rd November 2015) - Lee, Wayne; Al‐Dossary, Hisham; Raybaud, Charles; Young, Julia M.; Morgan, Benjamin R.; Whyte, Hilary E.A.; Sled, John G.; Taylor, Margot J.; Shroff, Manohar M.
Abstract : Purpose: To measure cerebellar growth in a longitudinal cohort of very preterm infants to identify early predictors of subsequent brain growth. Although the cerebellum grows rapidly during late gestation, the rate and variability of growth following premature birth, and the effects of associated injury, are largely unknown. Materials and Methods: In all, 105 very‐preterm born infants (24–32 weeks GA) were imaged using magnetic resonance imaging (MRI) at birth, term‐equivalent, 2, and 4 years of age. Cerebellar and total cerebral volumes were estimated from 1 mm isotropic T 1 ‐weighted scans acquired at 1.5T and 3T, using an atlas‐based approach. Linear models were used to analyze cerebellar volume as cross‐sectional and longitudinal functions of age, clinical, and radiological correlates. Linear models were also used to test for associations between volume and cognitive outcome. Results: Cerebellar volume increased rapidly with age‐at‐scan during both the preterm (0.7 mL/wk, P < 0.001) and term periods (1.8 mL/wk, P < 0.001). Infants with grade 3 or 4 germinal matrix hemorrhage (GMH) had smaller cerebellar volumes as a percentage of total brain volume starting at birth and continuing to 4 years of age (–0.43%, –0.57%, –1.09% at preterm, term, and 4 years, respectively, P < 0.01). Irrespective of age‐at‐scan, early cerebellar volume was predictive of volume at 4 years of age (slope = 1.3, P < 0.001). Cerebellar volumes were not found to predict cognitive outcome at 4 years of age; P < 0.2. Conclusion: High‐grade GMH and small perinatal cerebellar size is predictive of cerebellar development up to 4 years of age. These findings suggest that it is possible to identify individuals at high risk of reduced cerebellar volumes at an early age. J. Magn. Reson. Imaging 2016;43:1462–1473.